2012
DOI: 10.1248/bpb.b12-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of <i>Leonurine</i> on L-Type Calcium Channel in Rat Ventricular Myocytes

Abstract: Leonurine (Leo) is a special alkaloid principle of Herba leonuri that has recently been suggested to improve cardiovascular functions. To date, there is no direct ionic evidence of Leo on regulating calcium channels in the heart. In the present study, we examined the effects of Leo on action potentials and membrane currents recorded from isolated rat ventricular myocytes with the whole-cell patch clamp technique. Leo 100 µM shortened the action potential duration in a dose-dependent manner. Leo up to 200 µM ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…Previous studies have demonstrated that SCM-198 ameliorates atherosclerosis, inhibits osteoclastogenesis, and prevents osteoporosis. 3234 Consistent with the previous studies, 35,36 our findings demonstrated that SCM-198 could increase the heart rate, ±dp/dt max , Vpm, and L0. In vivo , we observed that SCM-198 reduced the infarct size, which was recognized to be one of the frequently used clinical end-points to predict clinical outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated that SCM-198 ameliorates atherosclerosis, inhibits osteoclastogenesis, and prevents osteoporosis. 3234 Consistent with the previous studies, 35,36 our findings demonstrated that SCM-198 could increase the heart rate, ±dp/dt max , Vpm, and L0. In vivo , we observed that SCM-198 reduced the infarct size, which was recognized to be one of the frequently used clinical end-points to predict clinical outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Xin et al [9] found that leonurine could reduce I Ca,L , and the LTCCα 1C subunit down-regulation might contribute to altered calcium handling in leonurine-treated cardiomyocytes. Leonurine at 100 μM shortened the action potential duration in a dose-dependent manner.…”
Section: Leonurine and Ischaemic Heart Diseasesmentioning
confidence: 99%